The Molecular Basis of Antithrombin Deficiency in Belgian and Dutch Families - Jochmans, K.; Lissens, W.; Seneca, S.; Capel, P.; Chatelain, B.; Meeus, P.; Osselaer, J. C.; Peerlinck, K.; Seghers, J.; Slacmeulder, M.; Stibbe, J.; Loo, J. van de; Vermylen, J.; Liebaers, I.; De Waele, M. (Thrombosis and Haemostasis, 1998)
The molecular basis of hereditary antithrombin (AT) deficiency has been investigated in ten Belgian and three Dutch unrelated kindreds. Eleven of these families had a quantitative or type I AT deficiency, with a history of major venous thromboembolic events in different affected members. In the other two families a qualitative or type II AT deficiency was occasionally diagnosed.DNA studies of the AT gene were performed, using polymerase chain reaction single-strand conformation polymorphism (PCR-SSCP) analysis, followed by direct sequencing of the seven exons and intronexon junction regions. Six novel point mutations were identified: four missense, one nonsense mutation and a single nucleotide deletion near the reactive site, causing a frameshift with premature translation termination. In two kindreds the underlying genetic defect was caused by a whole gene deletion, known as a rare cause of AT deficiency. In these cases, Southern blot and polymorphism analysis of different parts of the AT gene proved useful for diagnosis. In another kindred a partial gene deletion spanning 698 basepairs could precisely be determined to a part of intron 3B and exon 4. In two type I and in both type II AT deficient families a previously reported mutation was identified. In all cases, the affected individuals were heterozygous for the genetic defect.